PENGARUH CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY DAN EMPLOYMENT PROTECTION TERHADAP AGRESIVITAS PAJAK PERUSAHAAN SERTA DAMPAKNYA TERHADAP NILAI PERUSAHAAN: - Nana Alhusna; Rheny Afriana Hanif; Ruhul Fitrios (Jurnal Aplikasi Akuntansi, 2023)
The study aims to learn how corporate tax aggressiveness is affected by corporate governance, CSR, and employee protections (Empirical Study on Agricultural and Mining Companies Listed on the Indonesia Stock Exchange in 2018-2020). Twenty-six companies were selected for this analysis using a systematic selection technique. This study used SPSS 25 for its statistical analysis, including multiple and simple linear regression. Tax aggressiveness affects company value, and although the board of directors has little bearing on the problem, audit committees do. Corporate social responsibility affects tax aggressiveness, as does employment protection